A Case of Accidental Fatal Aluminum Phosphide Poisoning Involving Humans and Dogs. Issue 3 (24th February 2015) - Behera, Chittaranjan; Krishna, Karthik; Bhardwaj, Daya Nand; Rautji, Ravi; Kumar, Arvind
Abstract Aluminum phosphide is one of the commonest poisons encountered in agricultural areas, and manner of death in the victims is often suicidal and rarely homicidal or accidental. This paper presents an unusual case, where two humans (owner and housemaid) and eight dogs were found dead in the morning hours inside a room of a house, used as shelter for stray dogs. There was allegation by the son of the owner that his father had been killed. Crime scene visit by forensic pathologists helped to collect vital evidence. Autopsies of both the human victims and the dogs were conducted. Toxicological analysis of viscera, vomitus, leftover food, and chemical container at the crime scene tested positive for aluminum phosphide. The cause of death in both humans and dogs was aluminum phosphide poisoning. Investigation by police and the forensic approach to the case helped in ascertaining the manner of death, which was accidental.